2012
DOI: 10.1007/s00268-012-1879-3
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Bowel Lengthening in Children with Short Bowel Syndrome: Systematic Review of the Bianchi and STEP Procedures

Abstract: Outcomes for intestinal lengthening procedures are very good, and increasingly so. However, further analysis is required in order to fully understand the relative strengths and weaknesses of each procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 79 publications
1
34
0
6
Order By: Relevance
“…The STEP procedure, reported by Kim in 2003, partially divides the dilated bowel transversely, serially and alternately in zigzag pattern using a transmesenteric approach with a possible increase in length of [100 % [7]. The STEP procedure [2,5] can be safely repeated in the event of recurrent significant bowel dilatation. A recent systematic review of both procedures by King et al [5] demonstrated a relatively low complication rate for obstruction, redilatation and perforation [1] at 17 % for the LILT Group and 26 % for the STEP group (p \ 0.02).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The STEP procedure, reported by Kim in 2003, partially divides the dilated bowel transversely, serially and alternately in zigzag pattern using a transmesenteric approach with a possible increase in length of [100 % [7]. The STEP procedure [2,5] can be safely repeated in the event of recurrent significant bowel dilatation. A recent systematic review of both procedures by King et al [5] demonstrated a relatively low complication rate for obstruction, redilatation and perforation [1] at 17 % for the LILT Group and 26 % for the STEP group (p \ 0.02).…”
Section: Discussionmentioning
confidence: 97%
“…The STEP procedure [2,5] can be safely repeated in the event of recurrent significant bowel dilatation. A recent systematic review of both procedures by King et al [5] demonstrated a relatively low complication rate for obstruction, redilatation and perforation [1] at 17 % for the LILT Group and 26 % for the STEP group (p \ 0.02). While survival was higher for STEP patients (89 vs 81 %, p \ .001) this was probably due to the greater severity of the illness for the LILT group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data gathered suggested that the percentage of patients weaned was significantly higher in the LILT group than in the STEP group. 27 The most recent lengthening and tailoring technique described is called Spiral Intestinal Lengthening and Tailoring (SILT). 28 Briefly spiral incision lines are drawn with a sterile marking pen at 451-601 to the longitudinal axis of a dilated small bowel segment.…”
Section: Short Bowel Syndromementioning
confidence: 99%
“…2013 yılındaki bir derleme sonucunda hem Bianchi hem de STEP uygulamasının bağırsak yetmezlikli hastalarda önemli seçenekler oldukları ortaya konmuştur ( Tablo 7), (56,(83)(84)(85)(86) .…”
Section: Lilt-step Karşılaştırmasıunclassified